2018
DOI: 10.2174/1745017901814010782
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Fine Needle Aspiration Cytology in Lesions of Oral Cavity and Salivary Glands: A Clinico-Pathological Study

Abstract: Objective:Fine Needle Aspiration Cytology (FNAC) is a rapid, reliable and safe diagnostic tool used for various lesions of the oral cavity and salivary glands. The present study was undertaken to categorize the cytomorphology of the oral cavity and salivary gland lesions on FNAC and to assess the accuracy of FNAC in arriving at a diagnosis.Materials and Methods:A prospective study on oral cavity swellings and salivary gland aspirates was done during a 2 year period from August 2015 to July 2017 in which a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(72 citation statements)
references
References 21 publications
0
72
0
Order By: Relevance
“…Its use is also well documented in the literature, with high levels of sensitivity and specificity reported. [17][18][19][20][21][22][23][24][25] Indeed, Deng et al used intra-oral FNA in 28 patients with benign and malignant oral and oropharyngeal lesions. The authors recorded sensitivity, specificity and accuracy values of 100 per cent, 95 per cent and 97 per cent, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its use is also well documented in the literature, with high levels of sensitivity and specificity reported. [17][18][19][20][21][22][23][24][25] Indeed, Deng et al used intra-oral FNA in 28 patients with benign and malignant oral and oropharyngeal lesions. The authors recorded sensitivity, specificity and accuracy values of 100 per cent, 95 per cent and 97 per cent, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly pertinent where additional information (beyond cytomorphology alone) is required, such as human papillomavirus (HPV) status in oropharyngeal squamous cell carcinoma cases, which requires P16 immunohistochemical staining of a cell block. 22,23,27 The Journal of Laryngology & Otology…”
Section: Discussionmentioning
confidence: 99%
“…It helps in avoiding surgical procedures in conditions such as nonneoplastic or inflammatory lesions and metastatic tumors 30‐32 . However, this technique has rarely been used in oral lesions 33‐37 . And to our knowledge, only two lingual actinomycosis cases have been reported diagnosed on FNAC and one by abscess drainage 4,13,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction in 1930, fine-needle aspiration cytology (FNAC) has gained acceptance over the years as a useful tool in the preliminary investigation of various lesions at different sites of the body. 1 2 3 This is largely due to its positive attributes, namely: relatively painless, easy to perform, can be employed in variety of patients including children and debilitated adult patients, it may not require anesthesia and associated complications are rare. 4 It is also relatively cheap, has high specificity and results are rapidly available making it an indispensable diagnostic and screening tool in resource scarce countries like Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“… 5 6 Despite these advantages and usefulness, however, it's been suggested that FNAC cannot replace histopathological examination (HPE) since the biological material obtained does not provide precise cellular architectural details, making HPE to be regarded as the gold standard for the diagnosis of a number of lesions. 2 7 …”
Section: Introductionmentioning
confidence: 99%